2020
DOI: 10.1186/s12890-020-01246-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhaler devices in asthma and COPD patients – a prospective cross-sectional study on inhaler preferences and error rates

Abstract: Background: Inhalation therapy is the backbone of asthma and COPD control. However, inhaler adherence and device mishandling continue to be a problem in real life. Some studies have shown that using a patient-preferred inhaler may reduce device handling errors and improve adherence to prescribed chronic inhaler drug therapy. The aim of this study was to compare the preferences for commonly used inhaler devices in Germany in patients with chronic obstructive respiratory disease. We also pursued the question whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 40 publications
(65 reference statements)
2
23
0
Order By: Relevance
“…These data highlight an unmet need in people with poor asthma-related QoL who seek user-friendly devices with clear feedback on correct drug administration. Our results, together with the findings of Hawken et al (15) and Schreiber et al (32), emphasize the need to improve the convenience, user-friendliness, and reliability of inhaler devices used to treat asthmatic patients.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These data highlight an unmet need in people with poor asthma-related QoL who seek user-friendly devices with clear feedback on correct drug administration. Our results, together with the findings of Hawken et al (15) and Schreiber et al (32), emphasize the need to improve the convenience, user-friendliness, and reliability of inhaler devices used to treat asthmatic patients.…”
Section: Discussionsupporting
confidence: 71%
“…Asthmatic patients from the Hawken series, placed most value on an inhaler that required one step for dose preparation rather than four steps, that is, was easy to use, gave a confirmation of the dose being taken, and could be used during episodes of breathing difficulties (15). Schreiber et al acknowledged that patients may vary in their inhaler preferences and established that the ease of handling, followed by short inhalation time and low inhalation resistance were the most important device features according to the patients included in their study (32). On the other hand, a recent study found that the fast relief of symptom and the reduction of exacerbation rate were considered the most important characteristics for asthma maintenance inhaler while ICS safety and device convenience were not identified as priority characteristic showing that patients put clinical efficacy in the first position (33).…”
Section: Discussionmentioning
confidence: 99%
“…Correct inhaler handling technique and device handling were contributed to symptom control of asthma. Ease of handling of inhaler is important to promote patient's acceptance [8]. This result confirms that many participants did not know to handle their inhalers correctly.…”
Section: Discussionsupporting
confidence: 59%
“…PMDI and DPI are each associated with their own advantages and disadvantages. The patient's preference for the inhaler device is determined by using the patient's skills preferences and experience with inhalers, available medication, and cost [8]. According to many studies, patients will not get the full value of their inhaled medications due to incorrect use of their inhalers, and it is considered to be a major public health problem [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation